2021
DOI: 10.3758/s13415-021-00966-x
|View full text |Cite
|
Sign up to set email alerts
|

The posterior cerebellum and temporoparietal junction support explicit learning of social belief sequences

Abstract: This study tests the hypothesis that the posterior cerebellum is involved in social cognition by identifying and automatizing sequences of social actions. We applied a belief serial reaction time task (Belief SRT task), which requires mentalizing about two protagonists' beliefs about how many flowers they receive. The protagonists' beliefs could either be true or false depending on their orientation (true belief: oriented towards and directly observing the flowers; or false belief: oriented away and knowing on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 57 publications
1
1
0
Order By: Relevance
“…In line with our hypothesis, our results confirmed that the posterior cerebellum contributes to memorizing social action sequences as opposed to simply reading and recognizing social actions that implied a consistent group stereotype. This finding extends prior research demonstrating the general role of the posterior cerebellar Crus in action sequencing along a large variety of social mentalizing tasks, most often without any a priori inherent order, including memorizing the temporal order of trait-implying actions (Pu et al, 2020(Pu et al, , 2021, predicting social action sequences based on personality traits (Haihambo et al, 2021), memorizing social trajectories involved in goal-directed navigation (Li et al, 2021), and even implicitly learning the order of others' beliefs (Ma et al, 2021b). Together, these studies confirmed the "sequence hypothesis" (Leggio & Molinari, 2015) applied to social cognition (Van Overwalle et al, 2019b), which states that the cerebellum identifies and encodes sequences of actions in the social domain.…”
Section: Cerebellar Crus and Memorizing The Sequence Of Social Actionssupporting
confidence: 83%
“…In line with our hypothesis, our results confirmed that the posterior cerebellum contributes to memorizing social action sequences as opposed to simply reading and recognizing social actions that implied a consistent group stereotype. This finding extends prior research demonstrating the general role of the posterior cerebellar Crus in action sequencing along a large variety of social mentalizing tasks, most often without any a priori inherent order, including memorizing the temporal order of trait-implying actions (Pu et al, 2020(Pu et al, , 2021, predicting social action sequences based on personality traits (Haihambo et al, 2021), memorizing social trajectories involved in goal-directed navigation (Li et al, 2021), and even implicitly learning the order of others' beliefs (Ma et al, 2021b). Together, these studies confirmed the "sequence hypothesis" (Leggio & Molinari, 2015) applied to social cognition (Van Overwalle et al, 2019b), which states that the cerebellum identifies and encodes sequences of actions in the social domain.…”
Section: Cerebellar Crus and Memorizing The Sequence Of Social Actionssupporting
confidence: 83%
“…Understanding this sequence is a process subserved by cerebellar sequencing functions–a necessary process that leads to the recognition of social signals and requires mentalizing about the intentions or beliefs behind these social cues. This idea has been corroborated by a variety of sequence-based mentalizing tasks (e.g., Pu et al, 2020 ; Haihambo et al, 2021 ; Heleven et al, 2021 ; Li et al, 2021 ; Ma et al, 2021a , b ). Several connectivity studies have uncovered bidirectional connections between the cerebellum and neocortical mentalizing areas which constitute the larger part of the default mode network ( Habas et al, 2009 ; Krienen and Buckner, 2009 ; Buckner et al, 2011 ; Van Overwalle and Mariën, 2016 ; Van Overwalle et al, 2019b , 2020 ).…”
Section: Introductionmentioning
confidence: 79%